Environmental assessment of pediatric Lead exposure in Tehran; a prospective cross-sectional study - Hedieh Ahangar; Afsoon Karimdoost; Amir Salimi; Maryam Akhgari; Scott Phillips; Nasim Zamani; Nasibeh Hassanpour; Ali-Asghar Kolahi; Gary R. Krieger; Hossein Hassanian-Moghaddam (BMC, 2021)
Abstract Background Ingestion and inhalation are common routes of exposure for lead in humans. Developing countries still have unacceptably high rates of lead toxicity, especially in children. Studies on probable risk factors of lead poisoning in Iranian children are insufficient. In this study, we aimed to evaluate possible environmental factors in children with high blood lead concentrations living in Tehran and neighboring cities. Methods In a prospective cross-sectional study between March 2018 and March 2019 we followed all children referred from two pediatric gastrointestinal clinics with blood lead level (BLL) > 5 μg/dL in metropolitan Tehran to investigate possible environmental risk factors in their home. Household specimens including scratched wall paint, house floor dust, windowsill dust, tap water, and consumed spice were evaluated using atomic absorption method to detect lead concentrations. Epidemiological and environmental data collected through in-depth interviews with parents/guardians. Industrial areas were defined based on municipality maps on industrial places. Results Thirty of 56 parents/guardians with BLL > 5 μg/dL agreed to be followed through environmental investigation. The only categorical statistically significant risk factor was a history of lead poisoning in the family and living in an industrial zone. There was a positive correlation between BLL and interior windowsills dust lead level, r = 0.46, p = 0.01. Scratched paint lead level and BLL showed a significant positive correlation, r = 0.50, p = 0.005. House floor dust lead level (median = 77.4, p < 0.001) and interior windowsill dust lead level (median = 291, p = 0.011) were both significantly higher than the environmental protection agency (EPA) standards of 40 μg/ft2, 250 μg/ft2. Interior windowsill dust lead concentrations were significantly higher in industrial areas (p = 0.026). Conclusion Children's playing environment should be cleaned more often to reduce dust. Moreover, specific rules may need to be implemented for paint lead concentrations and air pollution, especially in industrial areas.